How Will Research in Neuroscience Influence the Practice of Psychiatry in the Next Ten Years? - Jonathan O'Keeffe (Opticon1826, 2011)
Psychiatry differs from other clinical specialties in several important respects. At a basic level, physical examination of the body is conspicuously absent in psychiatry. The diagnostic process employs almost no physical laboratory-based tests such as blood, urine, or CSF (cerebrospinal fluid) analysis. Nor are the various imaging modalities instrumental in diagnosing a psychiatric condition. Such investigations are almost ubiquitous elsewhere in medicine, yet insofar as they are utilized in psychiatry they are overwhelmingly aimed at excluding non-psychiatric conditions. Moreover, modern-day psychiatry is, more than any medical specialty, a minefield of controversy. Psychoanalysis, for example, still widely practised, is viewed by many psychiatrists in the field as little more than quackery (Webster 1996), and even within the disciplined ranks of those committed to neurobiological models of disease disagreement exists as to whether schizophrenia and bipolar disorder represent distinct pathologies (Maier, Zobel and Wagner 2006). As if the unusual nature and degree of internal debate regarding psychiatric theories and therapies were not enough, controversy extends so far as to question the very existence of psychiatric conditions. As Thomas Szasz, Professor of Psychiatry at Syracuse University, famously opined, '“mental illness” is not the name of a biological condition' (Szasz 1973).